2016
DOI: 10.1039/c5cs00659g
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative photoredox catalysis

Abstract: Visible-light photoredox catalysis has been experiencing a renaissance in response to topical interest in renewable energy and green chemistry. The latest progress in this area indicates that cooperation between photoredox catalysis and other domains of catalysis could provide effective results. Thus, we advance the concept of cooperative photoredox catalysis for organic transformations. It is important to note that this concept can bridge the gap between visible-light photoredox catalysis and other types of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(124 citation statements)
references
References 53 publications
(55 reference statements)
1
118
0
Order By: Relevance
“…Using other light sources, such as CFLs or UVA lamps, led to lower efficiency. Interestingly, addition of external photosensitizers 2 to the reaction mixtures and use of UV-induced dimeric gold species 3e resulted in diminished yields. Investigation of the scope of this transformation indicated that substrates bearing both electron releasing- ( 90b ) and withdrawing substituents ( 90c ), as well as sensitive functionalities ( 90d-e and 90g ), were well tolerated.…”
Section: Visible Light-induced Au-catalyzed Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using other light sources, such as CFLs or UVA lamps, led to lower efficiency. Interestingly, addition of external photosensitizers 2 to the reaction mixtures and use of UV-induced dimeric gold species 3e resulted in diminished yields. Investigation of the scope of this transformation indicated that substrates bearing both electron releasing- ( 90b ) and withdrawing substituents ( 90c ), as well as sensitive functionalities ( 90d-e and 90g ), were well tolerated.…”
Section: Visible Light-induced Au-catalyzed Reactionsmentioning
confidence: 99%
“…All of which have been previously reported under dual gold/photoredox catalysis. 2 Interestingly, oxyarylation of alkene 94 was performed under photoirradiation with Au-catalyst and resulted in moderate yield of 95 (Scheme 24c). In sharp contrast, Glorius previously reported that under visible light-induced Au-catalysis, oxyarylation of 94 required a PC in order to promote the reaction ( 96a ), without which only 4% of the oxyarylation product ( 96b ) was obtained.…”
Section: Visible Light-induced Au-catalyzed Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic transformations are afforded by combining photoredox with transition-metal complexes, or electrocatalysis [69]. Recently, photoredox has entered the realm of biocatalysis to form a more synergistic framework for catalysis of challenging reactions under mild conditions.…”
Section: Coupling Visible-light Photoredox Catalysis With Biocatalystsmentioning
confidence: 99%